Stimulation Of Early Childhood Social-Emotional Development With The Tellyng Story Method - Miranda Moni; Nofi Tefa; Idayanti Kargena; Itin Nenosaban; Angki Tolang; Fredericksen Victoranto Amseke (FKIP UNSULTRA, 2026)
Background: Social-emotional development is a fundamental aspect of early childhood education because it enables children to regulate emotions, cooperate with peers, communicate effectively, and establish positive social relationships. Storytelling is considered an appropriate child-centered learning method for fostering these competencies through meaningful and engaging learning experiences. Objective: This study aimed to examine the relationship between the implementation of the storytelling method and the social-emotional development of children aged 5–6 years at Cemara Liliba Kindergarten, Kupang City. Method: This quantitative study employed an ex post facto design involving 20 children selected through total sampling. Data were collected using structured observation and child development assessment instruments. Descriptive statistics and simple linear regression analyses were performed using SPSS version 25. Results: The findings revealed that the storytelling method had a positive and statistically significant relationship with children's social-emotional development (F = 6.155; p = 0.023 < 0.05; t = 2.481; p = 0.023). The coefficient of determination (R² = 0.255) indicated that storytelling explained 25.5% of the variance in children's social-emotional development, while 74.5% was influenced by other factors beyond this study. Novelty: This study provides empirical evidence regarding the contribution of storytelling to children's social-emotional development within an authentic kindergarten classroom context. Conclusion: Storytelling is an effective child-centered learning approach for promoting children's social-emotional development through meaningful, interactive, and engaging learning experiences.